PSYCHOLOGICAL MODEL OF FANTASY DEVELOPMENT IN YOUNGER SCHOOLCHILDREN - Chorna, Olena (Personality and environmental issues, 2024)
The article emphasizes the need to develop the imagination of younger schoolchildren as an important factor in the formation of their creative personality. It is emphasized that the younger school age is a sensitive period for the development of imagination, and therefore the task of modern elementary school is to use a period favorable for the development of this mental function. Based on a substantive analysis of theoretical and empirical scientific research by modern Ukrainian and foreign psychologists and teachers, current directions for studying the outlined problem are revealed. A psychological model of the development of imagination in younger schoolchildren in conditions of targeted psychological and pedagogical influence is presented. It consists of three blocks: target (the goal of formative influences is defined: the development of fantasy (verbal and non-verbal) in younger schoolchildren), operational-activity (internal factors are highlighted, in particular age, gender and individual-psychological characteristics of the personality (intelligence, self-esteem and level of aspirations, level of subjective control, introversion-extroversion, emotional lability-emotional stability, type of temperament, psychophysiological interhemispheric work of the brain)), external factors (peculiarities of family upbringing, nature and system of school education) and psychological and pedagogical conditions for the development of fantasy in students, educational and advisory measures for teachers, parents, psychologists, means of developing students' fantasy) and effective (qualitative indicators (components) are reflected, in particular need-motivational, information-cognitive, goal-forming, operational-resultative, emotional-sensory) and quantitative indicators (levels) of the development of students' imagination). In the process of research, a conclusion was made about the leading role of the teacher in the development of the imagination of younger schoolchildren, in particular, in providing them with the necessary psychological and pedagogical conditions for this.